Coexistence of linear and inversus variants of lichen planus pigmentosus: A rare occurrence - Anuradha Bishnoi; Davinder Parsad; Uma Nahar Saikia; Muthu Sendhil Kumaran (Wolters Kluwer Medknow Publications, 2019)
Lichen planus pigmentosus (LPP) is a rare disorder affecting primarily the people with ethnic skin. It results in hyperpigmentation of sun-exposed sites along with the involvement of flexures. In accordance with clinical patterns, different variants such as diffuse, blotchy, reticulate, and perifollicular have been described. Rare variants such as flexural (inversus), mucosal, linear, and zosteriform have been reported scarcely. Inversus LPP refers to the involvement of major flexures such as inframammary area, axillae, and groins in the absence of involvement of photo-exposed sites. We present an unusual case presenting with coexisting linear and inversus variants of LPP.